PENGARUH SISA LEBIH PEMBIAYAAN ANGGARAN (SiLPA) DAN DANA PERIMBANGAN TERHADAP BELANJA LANGSUNG PADA PEMERINTAH KABUPATEN DELI SERDANG - Dwi Saraswati (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2021)
This research was conducted at the Regional Financial and Asset Management Agency of Deli Serdang Regency. This study aims to examine and find the effect of excess budget financing (SiLPA) and Balancing Funds on direct spending. The population in this study were the Dinas and Districts in Deli Serdang Regency in 2016 - 2018, the population in this study was 52 offices and sub-districts in Deli Serdang Regency. The sampling technique in this study used the purposive sampling method with the criteria of having data from the SiLPA and Balancing Fund reports for 3 (three) consecutive years, namely from 2016 to 2018, the number of samples was 52 x 3 years = 156 samples consisting of 52 Department / District of Deli Serdang Regency. The research method used is a quantitative method. Data processing uses the SPSS version 2.0 application by performing the Classical Assumption Test, Normality Test, Heteroscedasticity Test, Multicollinearity Test, Autocoleration Test, Multiple Regression Analysis, Partial Test (t test), Simultaneous Test (f test), and Determinant Test (R2). Partially the test results show that the excess budget financing (SiLPA) and the Balancing Fund have a significant effect on direct expenditure. Then simultaneously the Excess Budget Financing (SiLPA) and Balancing Funds have a significant effect on Direct Expenditures.